Mutagenic potential of Gamma rays on Somatic cell division and morphological parameters in Foeniculum vulgare Mill. - Mishra, Moni; Kumar, Girjesh (Current Botany, 2021)
Mutagenesis involving ionizing radiation has been widely used for alteration in genetic constituents to increase the variability at gene level in a very small fraction of time. But, attempts to induce genetic variability in fennel for agronomically important trait are very limited. Narrow genetic base is the main hindrance in handling the conventional breeding in Fennel . Thus, main idea of this study is to generate genetic variability in Ajmer fennel-2 variety of Foeniculum vulgare Mill. by using the most potent physical mutagen i.e. gamma rays. The seeds were exposed to different doses of gamma rays viz. 5, 10, 15, 20 and 25Kr, respectively, along with control to analyze the effect of gamma rays on meristematic root tips. Germination and survival percentage were significantly affected in response to ionizing potential of gamma rays and a dose dependent decline was observed in both the parameters. Plant height, shoots, root length and days of flowering were also affected by gamma rays and a considerable increment was achieved at lowest dose with respect to control. As the dose of gamma ray increases, the rate of Active Mitotic Index declines. The irradiated seeds show numerous chromosomal variations such as; scattering, stickiness, bridge formation etc which are computed in the form of Total Abnormality Percentage.